2018
DOI: 10.1002/suco.201800100
|View full text |Cite
|
Sign up to set email alerts
|

Postcracking tensile behavior of blended steel fiber‐reinforced concrete

Abstract: Fiber blends have the potential to improve the mechanical and sustainability credentials of steel fiber‐reinforced concrete (SFRC), but at which ratios these can work is not known a priori. This paper investigates the uniaxial tensile stress–strain ( σ − ε) relationship of blended SFRC using manufactured steel fibers on their own, or blended with sorted steel fibers recycled from end‐of‐life tires (recycled tire steel fiber [RTSF]), at total fiber dosages of 30, 35, and 45 kg/m3. The accuracy of two σ − ε rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Despite the variations found in the different SFRSCC, there were no major changes promoted by the addition of fibers in the compressive strength of the concrete. The same was observed in the concretes produced by Hu et al [20].…”
Section: Compressive Strengthsupporting
confidence: 81%
“…Despite the variations found in the different SFRSCC, there were no major changes promoted by the addition of fibers in the compressive strength of the concrete. The same was observed in the concretes produced by Hu et al [20].…”
Section: Compressive Strengthsupporting
confidence: 81%
“…In addition, Eldin and Senouci (1994) observed that the control specimens were broken into two pieces under loading while the rubberized concrete did not show brittleness under flexural loading. Moreover, Hu et al, (2018) reported that the addition of specific ratios of blended steel fibres in concrete improved the mechanical properties.…”
Section: Cracking Behaviour and Failurementioning
confidence: 99%
“…However, not all of these methods have been integrated into developed software, which generally requires considerable theoretical knowledge and programming expertise. Moreover, the damaged plasticity model, integrated into the commercial FEM software ABAQUS, 10 has been widely applied to analyze the damage evolution and plastic deformation processes of concrete structures, [11][12][13][14][15][16][17][18][19][20][21] such as reinforced concrete tunnel linings under earthquakes, [22][23][24][25] blasts, [26][27][28] impact, 29 and high water pressures. 30 The yield condition in this constitutive model is controlled by the Lubliner SC, which was first proposed by Lubliner et al 31 and Oller et al 32 (the Lubliner-Oller SC), later modified by Lee and Fenves 33 (the Lubliner-Lee SC) aimed at the concrete failure surface in multiaxial stress states.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38] Validation results have demonstrated that the Lubliner SC successfully reproduces nonlinear concrete behavior under various loading conditions. However, this SC is focused more on tensiondominated fracture and deformation under a low confining pressure [11][12][13][14][15][16][17][18][19][20][21] than on the effect of compressive damage and plasticity considering concrete elements in multiaxial stress states. Moreover, its implementations have mainly been limited to nontriaxial compression problems, and little attention has been paid to its applicability in triaxial compressive stress states.…”
Section: Introductionmentioning
confidence: 99%